2008
DOI: 10.1097/gim.0b013e318187760f
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal translocations: tracing their meiotic behavior

Abstract: Purpose: Segregation and interchromosomal effect studies have been performed in reciprocal translocation carriers by sperm-fluorescent in situ hybridization reporting a great heterogeneity. The divergences have been attributed to the particular cytogenetic characteristics of each rearrangement. Nevertheless, there is no consensus in the factors that are responsible for such variability. The purpose of this study was to determine which cytogenetic features influence in the segregation and interchromosomal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 43 publications
1
28
2
1
Order By: Relevance
“…The analysis of results from reciprocal translocation carriers revealed no overall difference in aneuploidy rate compared to the appropriate control group ( P  = 0.87). Some previous findings obtained using FISH analysis of small numbers of chromosomes, mostly carried out in sperm, have suggested that reciprocal translocations can be associated with an ICE [9], [12], while other investigations have reported opposite findings [8], [16], [17]. The current study suggests that most reciprocal translocations are probably not associated with an ICE, but does not rule out the possibility that translocations involving specific breakpoints/chromosomal regions might exhibit this phenomenon.…”
Section: Resultscontrasting
confidence: 88%
See 2 more Smart Citations
“…The analysis of results from reciprocal translocation carriers revealed no overall difference in aneuploidy rate compared to the appropriate control group ( P  = 0.87). Some previous findings obtained using FISH analysis of small numbers of chromosomes, mostly carried out in sperm, have suggested that reciprocal translocations can be associated with an ICE [9], [12], while other investigations have reported opposite findings [8], [16], [17]. The current study suggests that most reciprocal translocations are probably not associated with an ICE, but does not rule out the possibility that translocations involving specific breakpoints/chromosomal regions might exhibit this phenomenon.…”
Section: Resultscontrasting
confidence: 88%
“…Several studies looking at sperm, have considered the mechanisms that might give rise to an ICE during meiotic divisions [9], [11]. This work has provided an insight into why certain segregation modes are favoured in patients with different types of rearrangement, but the reason why some male translocation carriers display an ICE in their sperm and others do not remains obscure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data show divergent results regarding the occurrence and distribution of ICE among carriers. Whereas some authors have observed a significant increase of numerical abnormalities for many of the chromosomes analyzed [Rousseaux et al 1995a;Rousseaux et al 1995b;Van Hummelen et al 1997;Blanco et al 1998;Mercier et al 1998;Blanco et al 2000;Amiel et al 2001;Morel et al 2001;Oliver-Bonet et al 2001;Baccetti et al 2002;Oliver-Bonet et al 2002;Anton et al 2004a;Anton et al 2004b Machev et al 2005;Anton et al 2006;Chen et al 2007;Wiland et al 2007;Anton et al 2008;Vozdova et al 2008;Juchniuk de Vozzi et al 2009;Anton et al 2010;Pellestor et al 2011;Vozdova et al 2011b], others have not [Martini et al 1998;Cifuentes et al 1999;Honda et al 1999;Estop et al 2000;Rives et al 2003;Mikhaail-Philips et al 2004;Oliver-Bonet et al 2004;Mikhaail-Philips et al 2005;Hatakeyama et al 2006;Kekesi et al 2007;Vialard et al 2007].…”
Section: Interchromosomal Effectmentioning
confidence: 96%
“…In a previous study performed in our laboratory in the largest series of reciprocal translocation carriers analyzed so far [Anton et al 2008 features where analyzed according to the occurrence of ICE: symmetry of the tetravalents, reorganizations involving acrocentric chromosomes, or participation of chromosomes with large blocks of heterochromatin (chromosomes 1, 9, and 16). None of these specific cytogenetic features correlated with increased rates of gametes with numerical anomalies.…”
Section: Reciprocal Translocations Carriersmentioning
confidence: 99%